2014
DOI: 10.1111/imb.12119
|View full text |Cite
|
Sign up to set email alerts
|

The sensory neurone membrane protein SNMP1 contributes to the sensitivity of a pheromone detection system

Abstract: Male moths detect female-released sex pheromones with extraordinary sensitivity. The remarkable sensory ability is based on a cooperative interplay of pheromone binding proteins in the lymph of hair-like sensilla trichodea and pheromone receptors in the dendrites of sensory neurones. Here we examined whether in Heliothis virescens the so-called 'sensory neurone membrane protein 1' (SNMP1) may contribute to responsiveness to the pheromone component, (Z)-11-hexadecenal (Z11-16:Ald). By means of immunohistochemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(94 citation statements)
references
References 41 publications
2
85
0
1
Order By: Relevance
“…odorant receptors, soluble proteins (odorant binding proteins: OBP, pheromone binding proteins: PBP), and sensory neuron membrane proteins (SNMP) are thought to be involved in sensitive odorant detection in insects (Benton et al, 2007;GrosseWilde et al, 2007;Jin et al, 2008). Most recently, it was suggested that the application of these biological molecules possibly increase the sensitivity of heterologous cells expressing insect odorant receptors (Pregitzer et al, 2014). Thus, by utilizing the functions of these biological molecules, we could enhance the sensitivity of cell-based odorant sensor elements established in this study.…”
Section: Sensitivity and Dynamic Rangementioning
confidence: 85%
“…odorant receptors, soluble proteins (odorant binding proteins: OBP, pheromone binding proteins: PBP), and sensory neuron membrane proteins (SNMP) are thought to be involved in sensitive odorant detection in insects (Benton et al, 2007;GrosseWilde et al, 2007;Jin et al, 2008). Most recently, it was suggested that the application of these biological molecules possibly increase the sensitivity of heterologous cells expressing insect odorant receptors (Pregitzer et al, 2014). Thus, by utilizing the functions of these biological molecules, we could enhance the sensitivity of cell-based odorant sensor elements established in this study.…”
Section: Sensitivity and Dynamic Rangementioning
confidence: 85%
“…In addition to pheromone receptors, SNMP1, which shows widespread conservation among insects (Rogers et al, 1997; Nichols and Vogt, 2008; Andersson et al, 2013; Jiang et al, 2016), is important for pheromone reception in both D. melanogaster and moths (Benton et al, 2007; Li et al, 2014; Pregitzer et al, 2014). Three non-mutually exclusive effects of SNMP1 on pheromone reception have been observed, namely (i) that SNMP1 is required for pheromone response (Benton et al, 2007), (ii) that it provides a more rapid onset and especially offset of response (Li et al, 2014), or (iii) that it increases the sensitivity of pheromone detection (Pregitzer et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…OSN responses to pheromone components may also require the presence of certain sensory neuron membrane proteins (SNMPs), which are integral membrane proteins related to scavenger proteins of the CD36 family (Benton et al, 2007; Jin et al, 2008; Nichols and Vogt, 2008). SNMP1 affects responses of pheromone receptors in Drosophila melanogaster and moths, but its role in pheromone reception at the molecular level is just beginning to be unraveled (Benton et al, 2007; Li et al, 2014; Pregitzer et al, 2014; Gomez-Diaz et al, 2016). Rapid advances in next-generation sequencing techniques have resulted in an accelerating number of insect species for which sequences of ORs and other proteins involved in chemoreception have been identified (Montagné et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SNMP1 subfamily is located on the membrane of pheromone-sensitive OSNs and is coexpressed with pheromone receptors, whereas the SNMP2 subfamily is expressed in the supporting cells surrounding the pheromonesensitive OSNs (Forstner et al, 2008). In the fruit fly Drosophila melanogaster and the moth Heliothis virescens, SNMP1 is essential for the detection of the pheromones 11-cis-vaccenyl acetate (cVA) and (Z)-11-hexadecenal, respectively (Benton et al, 2007;Jin et al, 2008;Pregitzer et al, 2014). However, the function of SNMP2 is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%